(untitled) - McNamara, Dennis L. (Ithaca, 1995)
Providing the fullest English-language account of Japanese textiles, Dennis L. McNamara explores the entire sweep of the industry, from the factory to the high-fashion brokerage to the policymaking circle. Tracing the strategies by which the textile industry has survived, he provides a distinctive view of Japanese capitalism in a climate of change. McNamara reconstructs a world riven by the competing interests of state and capital, firm and industry, labor and management, mill and merchant. We encounter giant "mogul" companies and upstart independent "mavericks" - such firms as Toray, Toyobo, Itochu, Tsuzuki, Kondobo, Onward, and Renown - all hustling to restructure for survival.Drawing on extensive interview data as well as recent Japanese and English-language work in political economy and social anthropology, McNamara describes a dynamic of competition between moguls and mavericks in a turbulent business torn by divisions but bound together by compromise. He finds that, despite enormous international pressures, the industry has maintained much of its market share, largely because state bureaucrats and leaders of major firms have managed to create a cooperative politics of adjustment. A corporatist structuring of interests, he concludes, has helped to moderate decline and maintain stability, permitting survival among the moguls without preventing the successful participation of mavericks.
Keywords: Ngành dệt may,Textile industry; Nhật Bản,Japan